PENGEMBANGAN KAPASITAS PETANI TERHADAP PENERAPAN BIOTEKNOLOGI TEBU DI WILAYAH BESUKI JAWA TIMUR - Pairan Pairan; Sri Yuniati; Djoko Susilo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Jember)
The decrease of sugar cane productivity is caused by the unavailability of superior seeds. Through the development of agricultural biotechnology is believed to be able to increase sugar cane production, in addition to manage time, cost, and energy. But sugarcane biotechnology is not necessarily acceptable to farmers. This study aims to research about farmers’s responses and impacts of sugar cane biotechnology and develop a model of capacity building of farmers on the application of sugar cane botechnology. The research data was collected through observation, interview, and documentation. Data analysis is done qualitatively with interactive model. Based on the results of research, it can be stated that the application of biotechnology will be supported by farmers during the sugar cane biotechnology can provide benefits to farmers. However, the application of biotechnology also raises the concerns of farmers on the socio – economic and cultural impact that will be received. Therefore, the application of sugar cane biotechnology must be supported by the development of farmers's capacity as it relates to the process of transforming new knowledge and technology. The capacity building model of farmers is done through three stages: awareness stage, capability transformation stage, and capability improvement stage. Through capacity building, farmers are expected to be able to reduce resistance to the application of sugar cane biotechnology.